2019
DOI: 10.3390/ceramics2020020
|View full text |Cite
|
Sign up to set email alerts
|

Ice-Templating for the Elaboration of Oxygen Permeation Asymmetric Tubular Membrane with Radial Oriented Porosity

Abstract: An original asymmetric tubular membrane for oxygen production applications was manufactured in a two-step process. A 3 mol% Y2O3 stabilized ZrO2 (3YSZ) porous tubular support was manufactured by the freeze-casting technique, offering a hierarchical and radial-oriented porosity of about 15 µm in width, separated by fully densified walls of about 2 µm thick, suggesting low pressure drop and boosted gas transport. The external surface of the support was successively dip-coated to get a Ce0.8Gd0.2O2−δ – 5mol%Co (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…SEM images in Figure show aligned pores perpendicular to the surface of the substrates, thus confirming that the freeze‐casting method was also effective to prepare tubular geometries, as already reported in other studies . The perpendicular pore alignment was consistent for all samples irrespective of the solid loading.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…SEM images in Figure show aligned pores perpendicular to the surface of the substrates, thus confirming that the freeze‐casting method was also effective to prepare tubular geometries, as already reported in other studies . The perpendicular pore alignment was consistent for all samples irrespective of the solid loading.…”
Section: Resultssupporting
confidence: 87%
“…Most experiments in freeze‐casting reports are for the production of flat or cylindrical ceramic substrates, though the majority of ceramic substrates for inorganic membrane application have tubular geometries. Nevertheless, there are a limited number of reports for the production of freeze‐cast tubular ceramic substrates . In a few reports, Liu et al produced mullite tubes and Dong et al prepared tubular porous silicate cement.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, highly anisotropic freeze-cast materials have been explored for development of biomimetic materials [8][9][10] and biomaterials 11,12 . Other applications focused on the high connectivity and tortuosity of macropores in freeze-cast materials for mass transport processes 13 , such as membrane manufacture [14][15][16][17] . The use of these materials for fuel cell electrodes has also been demonstrated 13,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Three of the papers of this issue are focused on demonstrating the benefits of ice-templating for specific applications. Gaudillere et al [8] investigated how ice-templating can be used to prepare oxygen permeation asymmetric tubular membrane. This particular application has been identified as promising for ice-templated ceramics, with studies reported from different groups [9,10].…”
mentioning
confidence: 99%